Effects of transaction and switching costs on mobile market performance - Arturo Basaure; Henna Suomi; Heikki Hämmäinen (International Telecommunications Society (ITS), 2014)
The exponential growth in demand of mobile Internet urges mobile network operators (MNOs) to increase the supply of wireless network capacity at a high pace. From this perspective, operators should not only obtain further network capacity but also make a more efficient use of the existing capacity. Latest developments in load balancing solutions address this challenge through two opposite evolution paths, cooperative and competitive. On the one hand, operator-driven cooperative solutions permit operators to trade spectrum capacity at wholesale level through e.g., Dynamic Spectrum Access (DSA) technologies. On the other hand, user-driven competitive solutions enable users to access and switch between different networks e.g., by adopting user multihoming capability and thereby intensifying retail competition. The deployment of these solutions determines the level of transaction and switching costs and consequently the level of retail competition and wholesale trading of spectrum capacity in a mobile market. This paper analyzes the effects of decreasing these costs in different mobile access scenarios, by employing agent-based modelling. Thus, the performed simulations aim to understand the effect of load balancing technologies on market performance. Finally, the paper suggests policy implications for different markets.
Keywords: 330; transaction costs; switching costs; load balancing; dynamic spectrum access; user multihoming; wholesale trading and retail competition